2015
DOI: 10.1021/acs.jpcb.5b09041
|View full text |Cite
|
Sign up to set email alerts
|

Polarizable Force Field with a σ-Hole for Liquid and Aqueous Bromomethane

Abstract: Bromomethane (CH3Br) is an acutely toxic environmental pollutant that contributes to ozone depletion. Molecular simulation could be a valuable tool for studying its partitioning and transport in the environment if an accurate molecular model was available. The generalized Amber force field (GAFF), OPLS (optimized potentials for liquid simulations) force field, and CHARMM general force field (CGenFF) were tested for their ability to model the physical properties of liquid bromomethane. The OPLS force field was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…Adluri et al showed that the GAFF model for bromomethane could be improved by reparameterizing the Lennard-Jones terms for Br. 55…”
Section: Halogensmentioning
confidence: 99%
“…Adluri et al showed that the GAFF model for bromomethane could be improved by reparameterizing the Lennard-Jones terms for Br. 55…”
Section: Halogensmentioning
confidence: 99%
“…The Lennard-Jones parameters are typically assigned empirically such that simulations using these parameters accurately predict the properties of representative bulk liquids (e.g., density, enthalpy of vaporization, dielectric constant, etc. ), 10,[12][13][14][15][16][17] although some QM-based approaches have also been applied. [18][19][20][21][22] A drawback of parameterizing Lennard-Jones parameters empirically is that they are generally underdetermined when molecules contain multiple types of atoms, allowing widely different parameters to be defined for them.…”
Section: Introductionmentioning
confidence: 99%
“…Lennard-Jones parameters for bromine are not optimal. 55 The bromine dispersion coefficients for the reparameterized force field were closer to the XDM values (206.7 a.u. and 163.1 a.u.…”
Section: Molecular Dispersion Coefficientsmentioning
confidence: 53%